1993
DOI: 10.1111/j.1365-2559.1993.tb00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell density and PGP 9.5‐immunostained nerves in angioleiomyoma: their relationship to painful symptoms

Abstract: Angioleiomyoma is frequently painful and the cause of the pain is unknown. The purpose of this study was to compare the mast cell population and innervation of painful and painless angioleiomyomas. Twenty-four cases of angioleiomyoma were examined; 16 painful and 8 painless cases. Pinacyanol erythrosinate and antibodies to protein gene product (PGP) 9.5 were used to demonstrate mast cells and nerves respectively. PGP 9.5-immunoreactive nerve fibres were found in most of the painful (13/16 cases) and painless l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Neviaser (31) reported a recurrence and malignant transformation 7 years after the initial operation requiring wide local excision. Herren et al (32) reported malignant transformation of an angioleiomyoma in the finger in a 17‐year old, which needed ray excision.…”
Section: Treatmentmentioning
confidence: 99%
“…Neviaser (31) reported a recurrence and malignant transformation 7 years after the initial operation requiring wide local excision. Herren et al (32) reported malignant transformation of an angioleiomyoma in the finger in a 17‐year old, which needed ray excision.…”
Section: Treatmentmentioning
confidence: 99%
“…Increased numbers of mast cells have been observed in biopsy specimens from about 20% of patients with Type I FIC 76 and IC, 28 and are thought by some to be involved in the pathophysiology of the syndrome 80 . The finding of mast cells in the bladder is by no means specific to these syndromes 81 . The role of mast cells in IC and comorbid disorders, especially those exacerbated by stress, was recently reviewed 82 .…”
mentioning
confidence: 99%
“…The association of nerve involvement with a tumor capsule and pain for angiomyomas has been similarly confirmed in other studies [ 19 ]. More specifically, a study by Geddy et al examined mast cell density in relation to incidents of painful angiomyomas determining that mast cell density was actually decreased in painful lesions, suggesting that mast cell degranulation may have occurred and potential local inflammation contributed to the development of lesion associated pain [ 20 ].…”
Section: Discussionmentioning
confidence: 99%